2020
DOI: 10.1016/j.tmaid.2020.101664
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional comparison of epidemiological and clinical features of patients with coronavirus disease (COVID-19) in Wuhan and outside Wuhan, China

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 26 publications
0
57
0
1
Order By: Relevance
“…Ninety‐two articles (of which four included pregnant patients) reported adult patients infected with SARS‐CoV‐2. Eleven articles included paediatric population, and four articles reported both adults and children infected with SARS‐CoV‐2 2,7,14‐118 . (Tables S1, S2 and S3) A total of 20 874 patients were included, of which 38 were pregnant patients, 395 were paediatric patients and the rest were adult patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ninety‐two articles (of which four included pregnant patients) reported adult patients infected with SARS‐CoV‐2. Eleven articles included paediatric population, and four articles reported both adults and children infected with SARS‐CoV‐2 2,7,14‐118 . (Tables S1, S2 and S3) A total of 20 874 patients were included, of which 38 were pregnant patients, 395 were paediatric patients and the rest were adult patients.…”
Section: Resultsmentioning
confidence: 99%
“…Seventy‐six articles, including 13 141 patients, described elevated liver chemistries at initial presentation 7,14‐34,46,47,49‐52,54‐75,77‐84,86,88‐93,102‐112 . The incidence of elevated liver chemistries varied from 1.1% to 68% in COVID‐19 patients 84,89 .…”
Section: Resultsmentioning
confidence: 99%
“…The lack of adequate medical resources became already evident in some developed countries and is more dramatic in the developing ones. It has been reported that in Guangzhou, China, where all patients with mild and moderate COVID-19 receive appropriate care and treatment at an early stage of the illness, their prognosis is better than that for patients in Wuhan, where they are more likely to be admitted to ICU and succumb to the disease (5). The difference between these two cities underscores the importance of appropriate care and treatment for early mild cases, particularly for patients at high risk of disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that patients in Guangzhou, China, had a better prognosis than in Wuhan. Patients in Wuhan were more likely to be admitted to an ICU and had higher mortality (5). This difference highlights the importance of appropriate care and treatment in early mild cases, especially in patients at high risk of disease progression.…”
Section: Introductionmentioning
confidence: 96%
“…Comparisons of COVID-19 epidemics among countries have been discussed in some articles [5][6][7]. The assumption of homogeneity of variance should be preliminarily ensured for the comparison of groups [8][9][10].…”
Section: Comparisons Of Covid-19 Epidemics and The Limitationsmentioning
confidence: 99%